Efforts for the Correct Comprehension of Deceitful and Ironic Communicative Intentions in Schizophrenia: A Functional Magnetic Resonance Imaging Study on the Role of the Left Middle Temporal Gyrus - Morese, R.; Brasso, C.; Stanziano, M.; Parola, A.; Valentini, M. C.; Bosco, F. M.; Rocca, P. (Frontiers in Psychology, 2022)
Deficits in social cognition and more specifically in communication have an important impact on the real-life functioning of people with schizophrenia (SZ). In particular, patients showed severe difficulties in communicative-pragmatics, for example in correctly inferring the speaker’s communicative intention in everyday conversational interactions. This limit was associated with morphologic and functional alteration of the left middle temporal gyrus (L-MTG), a cerebral area involved in various communicative processes, in particular in the distinction of ironic communicative intention from sincere and deceitful ones. We performed a fMRI study on 20 patients with SZ and 20 matched healthy controls (HC) while performing a pragmatic task testing the comprehension of sincere, deceitful, and ironic communicative intentions. We chose the L-MTG as region of interest. SZ patients showed difficulties in the correct comprehension of all types of communicative intentions and, when correctly answering to the task, they exhibit a higher activation of the L-MTG, as compared to HC, in all experimental conditions. This greater involvement of the L-MTG in the group of patients could depend on different factors, such as the increasing inferential effort required in correctly understanding the speaker’s communicative intentions, and the higher integrative semantic processes involved in sentence processing. Future studies with a larger sample size and functional connectivity analysis are needed to study deeper the specific role of the L-MTG in pragmatic processes in SZ, also in relation to other brain areas.